Public debt, child allowances, and pension benefits with endogenous fertility - Masaya Yasuoka; Atsushi Miyake (Kiel Institute for the World Economy (IfW), 2012)
The stock of public debt in some developed countries continues to increase because of a lack of tax revenues and the burdens of social security. Many of those developed countries suffer from lower birth rates. Child allowances might help to raise fertility, leading to higher tax revenue in the future because of an increase in the younger population. In this paper, the authors examine whether or not child allowances reduce the public debt stock as a share of Gross Domestic Product (GDP) in an economy with a pension system. As long as the long-run debt ratio is non-negative, child allowances financed by bonds always increase the public debt stock per unit of GDP.
Keywords: G23; H55; J13; 330; public debt; endogenous fertility; child allowances; pension